A laboratory application for teaching the effect of harmonics on transformer core saturation. Issue 3 (July 2020) - Dönük, Atilla
Harmonics in supply voltage or load current in a transformer have undesirable effects on the core and windings. As the harmonic content increases, higher core loss and eddy current loss in the windings results in higher operating temperatures. It causes magnetic flux density in the core to increase and shifts the operating point through the saturated region. This phenomenon is mostly taught in undergraduate education as theoretical information. However, as a difficult concept to understand, harmonics phenomenon might be taught by using experiments for active learning, visualizing the effects in a laboratory setting, and making the connection between theoretical and practical applications for deeper and meaningful learning. In this study, a teaching method for effects of harmonics is proposed and phase shift between the fundamental and harmonic component of the supply voltage on the transformer B–H characteristic in a laboratory application is introduced by an experimental work performed on toroidal transformers. Feedback from students shows that the proposed method is very efficient and useful for students to better understand the effects of harmonics on the transformer cores.